THE FIRST TUVAN DOCTOR: BIOGRAPHICAL TOUCHES - Маадыр, Мая Салчаковна; Хомушку, Сайдай Алексеевна (Medicine in Kuzbass, 2024)
The organization of healthcare in the Tuvan People’s Republic, a state that existed for twenty-three years (1921-1944), had its own socio-economic characteristics. At the same time, the key problem was personnel training, which was carried out mainly in Soviet educational institutions. Thus, it took twelve years to train the first Tuvan doctor.